Optimizing Adhesion of Laser Structured Plated Ni-Cu Contacts with Insights from Micro Characterization. (August 2016) - Büchler, Andreas; Kluska, Sven; Bartsch, Jonas; Cimiotti, Gisela; Brand, Andreas A.; Schubert, Martin C.; Glatthaar, Markus
Abstract: An improved understanding of the interface situation between metal and laser-structured semiconductor for nickel-copper plated solar cell contacts is created by micro characterization using SEM and Raman spectroscopy. A special focus is set on laser ablation with high energy density and the resulting mechanical contact adhesion. This aims to increase the flexibility of the process towards variable cell and emitter designs. The analysis revealed two neglected aspects. First, on laser openings that were created with high laser energy input the thickness of the native oxide exceeds the typical dimension of 1 nm. The oxide layer allows metal plating, but hinders the growth of nickel silicide and thus affects the mechanical properties of the contacts. As shown in this work the adhesion can be improved by a more thorough etching of the oxide before plating. Second, Raman spectroscopy revealed that the tension under the laser processed surfaces differs for varying energy inputs only after thermal silicidation was performed. Inadequately chosen laser parameters causes high tension in the laser treated silicon causing decreased adhesion. This work reveals the value of microscopic analysis for the optimization of laser processes for metallization.